Peer group clinical supervision: Qualitative perspectives from nurse supervisees, managers, and supervisors. Issue 4 (August 2021) - Saab, Mohamad M.; Kilty, Caroline; Meehan, Elaine; Goodwin, John; Connaire, Sinéad; Buckley, Carmel; Walsh, Anne; O'Mahony, James; McCarthy, Vera J.C.; Horgan, Aine
Abstract: Background: Clinical supervision helps promote practitioners' personal and professional development through fostering a supportive relationship and working alliance. Peer group clinical supervision is a form of clinical supervision whereby two or more nurses engage in a supervision process to improve their professional practice and provide quality care. Aim: To explore the experiences of supervision from the perspectives of nurse supervisees, their direct line managers, and clinical supervisors. Methods: A qualitative descriptive pragmatic design was used. Individual interviews and focus groups were conducted with 27 participants. Data were analysed using deductive content analysis. Findings: Three main categories were identified: Perceived benefits of peer group clinical supervision, challenges faced during peer group clinical supervision, and enhancements for future peer group clinical supervision sessions. Stress reduction, problem solving, managing change, and improved prioritisation were amongst the benefits gained from clinical supervision. Challenges included competing work demands, staffing issues, and the duration, location, and process of supervision. Participants recommended adding time to the allocated supervision hour, raising awareness of peer group clinical supervision in advance, and training expert supervisors. Discussion: The space for peer group clinical supervision needs to be primed beforehand through providing and ensuring protected time, the availability of experienced supervisors, and raising key stakeholders' awareness of what supervision entails. Stress caused by competing work demands and the fear of losing momentum need to be considered by services in advance. Conclusion: Findings support the planning, delivery, and evaluation of future peer group clinical supervision sessions, while addressing challenges identified by study participants.